Cost Efficient Partial CO2 Capture at an Integrated Iron and Steel Mill - Sundqvist, Maria; Biermann, Max; Ali, Hassan; Skagestad, Ragnhild; Normann, Fredrik; Larsson, Mikael; Nilsson, Leif (2019)
Mitigation of anthropogenic CO2 emissions is our time most important challenge. For large emission sources, such as the iron and steel industry, implementation of CO2 capture is often discussed as a mean to achieve low emission targets. However, a major obstacle is the cost associated with large scale capture. This article aims to show how capture cost can be lowered by smart integration of partial CO2 capture powered by excess heat associated into SSAB Europe’s integrated plant in Luleå. Three point sources were investigated; flue gas from hot stoves (HS), blast furnace gas (BFG), and flue gas from CHP plant. Compared to the two end-of-pipe scenarios, capture on BFG will improve the overall energy utilization, leaving room for more available steam to be used for capture which lowers the specific cost of CO2